Assessing the practice of trusted electronic records management in Malaysian government-controlled companies / Aliza Ismail - Ismail, Aliza (2010)
Trusted electronic records relates to the concept of reliability and authenticity where records need to be maintained and preserved as a mechanism of providing evidence and accountability. Records reliability reflects the trustworthiness of the content of record through the practice of good recordkeeping. Records authenticity guarantees the content has not been changed, altered or manipulated since their first creation through out their life cycle. Managing trusted electronic records is becoming an emerging issue to many organizations today. With the rapid growth of electronic communications and information systems, electronic records have presented new challenges in ensuring the survival of reliable and authentic records over time. The primary goal of this study is to establish and develop a robust framework for trusted electronic records management. A multiple case studies approach is utilized to examine the electronic records practices in six (6) Malaysian Government-Controlled Companies (MGCC). The findings from these cases lead the researcher to generate the trusted electronic records management framework. In summary, the study contributes to the understanding and the development of the framework which embraces the governance structure to provide the mandate, a policy framework and responsibilities of managing records in electronic environments, the people factor that requires specialist knowledge and skills to manage and exploit the records, information and knowledge assets of the organization effectively and efficiently, the good recordkeeping practices and systematic archival management to protect and preserve the organizational memory, the integration of the existing information systems to records management systems to ensure the integrity and the authenticity of those records produced in electronic environments. On top of this, top management leadership, endorsement and support are crucial as one of the critical success factors to undertake this endeavor.